Microbial mechanism of zinc fertilizer input on rice grain yield and zinc content of polished rice - Xiao, Yang Sean; Zhou, Bo; Han, Zhuangzhuang; Liu, Shenzhou; Ding, Can; Jia, Feifei; Zeng, Wenzhi (Frontiers in Plant Science, 2022)
Zinc is an essential minor element for rice growth and human health, which can also change the structure of the microorganisms. However, it remains unclear for the effects of zinc fertilizer on microbiome function in agricultural soils and crops. To solve this research gap, we investigated the relationship between improving rice (Oryza sativa L.) yield, Zn concentration, soil microbial community diversity, and function by the application of Zn fertilizer. The field trials included three rice varieties (Huanghuazhan, Nanjing9108, and Nuodao-9925) and two soil Zn levels (0 and 30 kg ha–1) in Jiangsu province, China. As a test, we studied the variety of soil bacterial composition, diversity, and function using 16S rRNA gene sequencing. The results showed that soil Zn application reduced the diversity of microbial community, but the bacterial network was more closely linked, and the metabolic function of bacterial community was improved, which increased the grain yield (17.34–19.52%) and enriched the Zn content of polished rice (1.40–20.05%). Specifically, redundancy analysis (RDA) and Mantel’s test results revealed soil total nitrogen (TN) was the primary driver that led to a community shift in the rice rhizosphere bacterial community, and soil organic carbon (SOC) was considered to have a strong influence on dominant phyla. Furthermore, network analysis indicated the most critical bacterial taxa were identified as Actinobacteria, Bacteroidetes, Proteobacteria, and Chloroflexi based on their topological roles of microorganisms. KEGG metabolic pathway prediction demonstrated that soil Zn application significantly (p < 0.05) improved lipid metabolism, amino acid metabolism, carbohydrate metabolism, and xenobiotic biodegradation. Overall, their positive effects were different among rice varieties, of which Nanjing-9108 (NJ9108) performed better. This study opens new avenues to deeply understand the plant and soil–microbe interactions by the application of fertilizer and further navigates the development of Zn-rich rice cultivation strategies.